Pendampingan Pengabdian Kepada Masyarakat Berbasis Islami di Desa Cipendawa dan Desa Cibeureum Kabupaten Cianjur - Mubarok, Wildan Fata; Syukron, Hanif; Al-Maududi, Izar; Reyhan, Muhammad; Firdaus, Aurandy Rachman; Nazir, Muhammad; Abdillah, Ronal (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2024)
Service aims to develop students’ abilities in improving teaching skills. Teaching to the community as a form of dedication to society and religious communities. Teaching to the community to help the community solve unanswered problems, to form a prosperous society, and life lessons for the surrounding community. Student involvement in the process of teaching knowledge to the community is a productive step towards achieving these goals. The research results indicate that involving students in maintaining and developing the teaching of knowledge through da’wah programs. This program not only improves the quality of teaching, but also helps increase students’ sense of responsibility towards religion and the community, as well as the knowledge gained during learning.